Pengembangan Rancangan Media Pembelajaran Augmented Reality Perangkat Jaringan Komputer - Melsi Sari Murfi; Kasman Rukun (Universitas Negeri Padang, 2020)
All The problem of the research is the absence of supporting learning media in learning activities of computer network, are not optimal mastery of concepts by students, and abstract teaching materials that need to be made more concrete, as well as using the use of smartphones in the 4.0 revolution industry. This study aims to develop learning media augmented reality and produce media that are valid, practical, and effective on computer network subjects so that they become alternatives as learning media. This research is a research and development (R&D) using the IDI model. Data analysis techniques for practicality using percentages, and effectiveness of the control class and the experimental class. In conclusion, the augmented reality learning media develop can valid, practical and effective to be used as a learning media on computer network subjects.